Comparing surgical interventions for interstitial cystitis: A systematic review. Issue 4 (8th April 2022) - Abelleyra Lastoria, Diego Agustín; Raison, Nicholas; Aydin, Abdullatif; Khan, Shamim; Dasgupta, Prokar; Ahmed, Kamran
Abstract: The purpose of this review was to summarize and compare the efficacy among surgical interventions in terms of symptomatic relief in patients with interstitial cystitis/bladder pain syndrome (IC/BPS). The review protocol was published on PROSPERO. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) 2020 checklist was followed. Following database search, a narrative synthesis was performed. Data pertaining symptom scores, pain levels, and voiding frequency following surgery were summarized by calculating percentage change in these parameters. Multiple surgical treatments were identified. These included injections of hyaluronic acid (HA), botulinum toxin A (Botox A), triamcinolone, resiniferatoxin (RTX), platelet‐rich plasma, and 50% dimethyl sulfoxide (DMSO) solution, neuromodulation, hydrodistension (HD), resection/fulguration of Hunner lesions, resection of ilioinguinal and iliohypogastric nerves, reconstructive surgery, and cystectomy. This review found no evidence suggesting that HD and RTX injections can ameliorate IC/BPS symptoms. Current evidence suggests that sacral neuromodulation, cystectomy, and transurethral resection/fulguration of Hunner lesions could lead to symptomatic relief in IC/BPS. Further research into the efficacy of Botox A, triamcinolone, 50% DMSO solution, and HA instillations is required. However, the best treatment options cannot be reliably stated due to the low level of evidence of the studies identified. Further research should report outcomes for Hunner‐type IC and BPS separately given their differing histopathological characteristics. Performing high‐quality randomized controlled trials could be hindered by the low prevalence of the condition and a small proportion of patients progressing to surgery.